2023
DOI: 10.1007/s00424-023-02804-0
|View full text |Cite
|
Sign up to set email alerts
|

A novel beneficial role of humanin on intestinal apoptosis and dysmotility in a rat model of ischemia reperfusion injury

Abstract: A prevalent clinical problem including sepsis, shock, necrotizing enterocolitis, and mesenteric thrombosis is intestinal ischemia/reperfusion (I/R) injury. Humanin (HN), a recently identified mitochondrial polypeptide, exhibits antioxidative and antiapoptotic properties. This work aimed to study the role of HN in a model of experimental intestinal I/R injury and its effect on associated dysmotility. A total of 36 male adult albino rats were allocated into 3 equal groups. Sham group: merely a laparotomy was don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 76 publications
1
0
0
Order By: Relevance
“…Moreover, Colivelin attenuated the inflammatory response, endothelial, and glycocalyx injury, and ameliorated glycocalyx density and mitochondrial structure among septic animals relative to shams. Similar findings were reported among male albino rats subject to an model of mesenteric artery ischemia reperfusion injury, wherein animals treated with HN analogue were reported to demonstrate reduced inflammation, apoptosis, and iNOS activity relative to shams (33). To the best of our knowledge, no studies have thus far evaluated whether HN directly influences platelet structure and function in shock and as such requires future mechanistic investigation.…”
Section: Discussionsupporting
confidence: 72%
“…Moreover, Colivelin attenuated the inflammatory response, endothelial, and glycocalyx injury, and ameliorated glycocalyx density and mitochondrial structure among septic animals relative to shams. Similar findings were reported among male albino rats subject to an model of mesenteric artery ischemia reperfusion injury, wherein animals treated with HN analogue were reported to demonstrate reduced inflammation, apoptosis, and iNOS activity relative to shams (33). To the best of our knowledge, no studies have thus far evaluated whether HN directly influences platelet structure and function in shock and as such requires future mechanistic investigation.…”
Section: Discussionsupporting
confidence: 72%
“…Similar ndings were reported among male albino rats subject to an model of mesenteric artery ischemia reperfusion injury, wherein animals treated with humanin analogue were reported to demonstrate reduced in ammation, apoptosis, and inducible nitric oxide synthase (iNOS) activity relative to shams. 25 To the best of our knowledge, no studies have thus far evaluated whether HN directly in uences platelet structure and function in shock. We observed that sHN was higher among patients with TAMOF phenotype relative to those without.…”
Section: Discussionmentioning
confidence: 99%